Advanced visual effects compositing : techniques for working with problematic footage - Lanier, Lee, ....- (New York : Routledge/Taylor & Francis Group, 2017)
In Advanced Visual Effects Compositing: Techniques for Working with Problematic Footage, learn to tackle difficult visual effect composites in layer-based and node-based compositing programs. In this book, industry veteran and compositing expert Lee Lanier offers tips, tricks, techniques, and workflows for difficult visual effects shots, including poorly shot green screen, moving shots with no visible motion tracking marks, shots requiring 3D elements that lack 3D renders, poor-quality stock footage, and incorrectly lit shots. Lanier details the common problems of visual effects shots and offers practical solutions using examples from Adobe After Effects and Blackmagic Design fusion. An accompanying eResource (www.routledge.com/9781138668348) features video image sequences, 3D renders, and other tutorial materials, allowing you to practice the discussed techniques. The visual effects challenges covered in this book include: Chroma keying, motion tracking, relighting in the composite, repairing plates, replicating damage, adding depth with 2.5D, working with stock footage.
"A Focal Press book"--cover.
Description based on print version record.
Keywords: Visual effects; compositing